2014
DOI: 10.1093/mnras/stu806
|View full text |Cite
|
Sign up to set email alerts
|

Iron and neutron-capture element abundance variations in the globular cluster M2 (NGC 7089)★

Abstract: We present CN and CH indices and Ca ii triplet metallicities for 34 giant stars and chemical abundances for 33 elements in 14 giants in the globular cluster M2. Assuming the program stars are cluster members, our analysis reveals (i) an extreme variation in CN and CH line strengths, (ii) a metallicity dispersion with a dominant peak at [Fe/H] ≈ −1.7 and smaller peaks at −1.5 and −1.0, (iii) star-to-star abundance variations and correlations for the light elements O, Na, Al and Si and (iv) a large (and possibly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
158
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(171 citation statements)
references
References 132 publications
11
158
2
Order By: Relevance
“…Although NGC 6273 is only at a distance of ∼9 kpc from the Sun (e.g., Piotto et al 1999), the large and highly variable reddening complicate both cluster RGB target selection and the interpretation of its color- 8 The term "iron-complex" refers to any globular cluster exhibiting a significant (0.10 dex) [Fe/H] dispersion when measured from high resolution spectra. We have adopted this term in order to avoid confusing the word "anomalous," which can refer to either a cluster with a metallicity dispersion (e.g., Marino et al 2015) or a sub-population with peculiar chemistry residing in a cluster (e.g., Pancino et al 2000;Yong et al 2014). We note that clusters with both [Fe/H] and s-process abundance spreads have also been referred to as "s-Fe-anomalous" .…”
Section: Observations and Target Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although NGC 6273 is only at a distance of ∼9 kpc from the Sun (e.g., Piotto et al 1999), the large and highly variable reddening complicate both cluster RGB target selection and the interpretation of its color- 8 The term "iron-complex" refers to any globular cluster exhibiting a significant (0.10 dex) [Fe/H] dispersion when measured from high resolution spectra. We have adopted this term in order to avoid confusing the word "anomalous," which can refer to either a cluster with a metallicity dispersion (e.g., Marino et al 2015) or a sub-population with peculiar chemistry residing in a cluster (e.g., Pancino et al 2000;Yong et al 2014). We note that clusters with both [Fe/H] and s-process abundance spreads have also been referred to as "s-Fe-anomalous" .…”
Section: Observations and Target Selectionmentioning
confidence: 99%
“…Combining the information from Figures 10 and 15 indicates that in all of the iron-complex clusters included here the increase in [La/Eu] is due to almost pure s-process enrichment. Previous work on iron-complex clusters such as M2 (Lardo et al 2013;Yong et al 2014), M22 (Marino et al 2009(Marino et al , 2011b, and NGC 5286 suggested that each may be decomposed into at least two populations: a low The similar heavy element abundance patterns observed for many iron-complex clusters makes it tempting to speculate that all of them formed through the same basic process. However, just as both normal and iron-complex clusters exhibit similar light element abundance variations but can have very different heavy element distributions, the similar s-process abundances of the iron-complex clusters could be a red herring.…”
Section: Comparison With Other "Iron-complex"mentioning
confidence: 99%
See 1 more Smart Citation
“…1999;Gratton et al 2001;Bedin et al 2004;Norris 2004;Piotto et al 2005;Mackey & Broby Nielsen 2007;Lee et al 2009;Da Costa et al 2014;See Gratton et al 2012 for a recent review). Most of the investigated GCs in the Galaxy are observed to show anti-correlations between light elements (e.g., C, N, and O) of cluster members stars (e.g., Carretta et al 2009; C09) whereas only 8 GCs have been so far confirmed to have star-to-star abundance spreads in heavy elements (e.g., Yong et al 2014;Marino et al 2015). Extended main-sequence turn-offs (eMSTOs) and splits in main-sequence observed in the color magnitude diagrams (CMDs) of some LMC GCs (e.g., Mackey & Broby ⋆ E-mail: kenji.bekki@uwa.edu.au Nielsen 2007; Goudfrooij et al 2014;Milone et al 2016) can be possible evidence for the multiple stellar populations with different ages, though recent observations suggest that internal stellar rotation rather than age spreads could explain the physical properties of LMC clusters with eMSTOs (e.g., Bastian & De Mink 2009;Milone et al 2016;Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Globular clusters (GCs) host mono-metallic 1 , almost coeval stellar populations that have been studied extensively, both ⋆ E-mail: angelou@mps.mpg.de 1 with a few exceptions, such as e.g., Omega Cenaturi (Johnson & Pilachowski 2010), M22 (Marino et al 2009), M54 (Carretta et al 2010a), M2 (Yong et al 2014) photometrically and spectroscopically. In spite of their multiple populations (see Gratton, Carretta & Bragaglia 2012), these systems offer well constrained tests for stellar evolution theory.…”
Section: Introductionmentioning
confidence: 99%